2021
DOI: 10.1029/2020jc017018
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into the Dynamics of the Radiating Internal Tide Associated With the Kuroshio Current

Abstract: Internal tides, generated by barotropic tidal currents flowing over abrupt topographic features (such as sills), are internal gravity waves that oscillate at tidal frequencies. The dissipating energy carried by propagating internal tides contribute a significant amount of mechanical energy to abyssal mixing and, hence, the general circulation (Polzin et al., 1997). For example, internal tides with spatial inhomogeneity and temporal variability largely induce a globally averaged diapycnal diffusivity of 10 −4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 62 publications
(93 reference statements)
0
21
0
Order By: Relevance
“…Incoherent ITs are caused by a non-linear interaction between varying background conditions and internal wave motions (Xu et al, 2016). Furthermore, the HKE of incoherent ITs can reflect the interaction between the background field and ITs (van Haren, 2004;Alford et al, 2015;Xu et al, 2021). Through harmonic analysis of the ITs, we can extract the coherent ITs, those with astronomical tide frequencies.…”
Section: Semidiurnal Itsmentioning
confidence: 99%
“…Incoherent ITs are caused by a non-linear interaction between varying background conditions and internal wave motions (Xu et al, 2016). Furthermore, the HKE of incoherent ITs can reflect the interaction between the background field and ITs (van Haren, 2004;Alford et al, 2015;Xu et al, 2021). Through harmonic analysis of the ITs, we can extract the coherent ITs, those with astronomical tide frequencies.…”
Section: Semidiurnal Itsmentioning
confidence: 99%
“…According to the average buoyancy frequency N = 6 cph, the magnitude order of the average diffusivity is O(10 −4 )-O(10 −3 ) m 2 s −1 and is consistent with our result. Yang et al (2014) observed diapycnal mixing on the continental shelf and slope and found that the average diffusivity can reach O(10 −3 ) m 2 s −1 too. Similar results have been reported in the study of internal solitary waves shoaling in other regions.…”
Section: Enhanced Diapycnal Mixing Induced By the Polarity Reversal Of Internal Solitary Wavesmentioning
confidence: 99%
“…Laurent, 2008). Observations show that high turbulence mainly occurs in the continental shelf region, and the average diffusivity can reach O(10 −3 ) m 2 s −1 , while the diffusivity in the continental slope region is 1 order of magnitude lower (Yang et al, 2014). When nonlinear internal waves travel cross the continental slope, their waveform changes into different types (Terletska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…15 of 20 ations are relatively large. These large standard deviations have resulted from the effects of seasonal changes of internal tides and variable pathways influenced by Kuroshio and mesoscale eddies (Alford et al, 2015;Huang et al, 2018;Xu et al, 2021).…”
Section: 1029/2021jc017878mentioning
confidence: 99%